2016
DOI: 10.1039/c6ay00381h
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Raman spectroscopy for the early detection of plant diseases: Abutilon mosaic virus infecting Abutilon sp.

Abstract: Plant diseases have a direct impact on the productivity of crops, and therefore the early detection of diseases is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…Utilization of spectral information was important for hyperspectral imaging application. Average spectra of each sample have been widely used in detecting plant diseases [ 40 ]. Use of average spectra of hyperspectral imaging was the same as Vis/NIR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of spectral information was important for hyperspectral imaging application. Average spectra of each sample have been widely used in detecting plant diseases [ 40 ]. Use of average spectra of hyperspectral imaging was the same as Vis/NIR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The differences was that the spectra of Vis/NIR spectroscopy were collected from a small part of the leaves [ 41 , 42 ] and each sample has one spectra averaged by several times of scans, while average spectra of hyperspectral imaging was acquired from a predefined region of interest (ROI) in the sample. The use of average spectra of infected samples had two situations, average spectra of the entire sample including the infected region and the healthy region within the sample, and average spectra of only the infected region [ 40 , 41 ]. The former was more effective, samples with or without visible symptoms could be predicted in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of Raman spectral peak position, amplitude, and area help understand the structure and content of organic molecules in plants . Yeturu et al studied the Raman spectra of velvetleaf and located its characteristic peaks using one‐way analysis of variance (ANOVA) method . Baranski et al analyzed carotenoid Raman peaks of vegetable tissue and found that the content of carotenoids in virus‐infected leaves were lower than that of healthy leaves .…”
Section: Introductionmentioning
confidence: 99%
“…14 Some salient applications of this technique include the study on the composition of materials in different areas, such as microbiology, arts, archaeology, geology, atmospheric sciences, and even planetary exploration, among many others. [15][16][17][18][19][20][21][22][23] Currently, also portable Raman spectrometers are available, with short acquisition times and reasonable spectral resolutions, thus providing reliable information on the characteristics of the measured material in short time. In a recent article, Morillas et al 24 have used a portable Raman spectrometer to evaluate the deterioration of building materials.…”
Section: Introductionmentioning
confidence: 99%